Teaching Reform of "Work-Integrated Learning" in International Trade Practice from the Perspective of BDaaS. (23rd December 2021) - Zhu, Yiting
Abstract : To improve the reform performance of international trade practice, the method with perspective of big data is researched in this study. The international trade professional is developing rapidly to keep pace with social development gradually. With the further development of the society, the traditional international trade major exposed some shortcomings, such as course training target, content and teaching method, and so on, which have fallen behind the progress of society. However, the perspective BDaaS is applied in this study to solve this problem, and the experiment results show that the proposed method will effectively improve the ability of cultivating international trade professionals.